Automatic accident location detection system (AALDS) - Goh, K.N. (Institute of Electrical and Electronics Engineers Inc., 2014)
Road transportation has revolutionized the way we travel and transport goods. The increasing number of road users is proportionate with the increasing number of accidents, which could include fatalities. MERS 999 is an effort by the Malaysian government to integrate all the emergency number service system. Reporting accidents has its challenges; mainly there exist communication gap in relaying location information to the operator. This, in turn, causes slow response to the situation. In addition, airbag crash sensors cover only limited angles, which detects frontal and side collision. The objective of this paper is to develop an integrative system that is able to speed up the process of reporting accidents. Our prototype, named as Accident Location Detection System (AALDS) includes an accident locator device, accident management website and SMS system. A hardware prototype was developed using components like auto-dialer, accelerometer, GPS and GSM components. Haversine algorithm was modified to enable better efficiency in searching the nearest hospital to the accident location. Results from our system testing have revealed time saving of 60 in comparison to MERS 999. The functionalities of this system will enhance the current emergency response service by providing a platform for reporting and responding to accidents efficiently. This will enable the authorities to provide faster medical attention to the public, which will reduce fatality rate. Â© 2014 IEEE.